2007
DOI: 10.1021/la700839p
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Bilayers as Biomembrane-like Barriers in Layer-by-Layer Polyelectrolyte Films

Abstract: Dipalmitoylphosphatidylcholine (DPPC) bilayer was created on the surface of an exponentially growing poly(glutamic acid)/poly(lysine) (PGA/PLL) layer-by-layer polyelectrolyte film. The lipid bilayer decreased the surface roughness of the polyelectrolyte film. The layer-by-layer construction of the polyelectrolyte film could be continued on the top of the DPPC layer. The lipid bilayer, however, formed a barrier in the interior of the polyelectrolyte film, which blocked the diffusion (a prerequisite for exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
(64 reference statements)
1
22
0
Order By: Relevance
“…Planar supported bilayers were built up (Dufrene and Lee 2000;Pilbat et al 2007), or natural membranes isolated from bacteria and anchored to flat surfaces (Müller et al 2000;Végh et al 2011) were used as models of biological membranes of bacterial cells. The effect of different cationic antimicrobial peptides has already been studied on planar lipid bilayers of different compositions (Shaw et al 2008;Végh et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Planar supported bilayers were built up (Dufrene and Lee 2000;Pilbat et al 2007), or natural membranes isolated from bacteria and anchored to flat surfaces (Müller et al 2000;Végh et al 2011) were used as models of biological membranes of bacterial cells. The effect of different cationic antimicrobial peptides has already been studied on planar lipid bilayers of different compositions (Shaw et al 2008;Végh et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…5 The main drawback of solid supports is that typical distances between the membrane and the substrate range up to 1 nm, 6,7 which is generally not enough to prevent the denaturing of transmembrane proteins. 7 In the effort to space the membrane up from the silicon substrate polymeric cushion materials that can form hydrated thin films such as polyacrylamide, 8 dextran, 9 agarose, 10 polyethyleneimine, 11,12 cellulose derivatives, 13 and poly͑ethylene glycol͒, [15][16][17] as well as polyelectrolyte multilayers, 18,19 have been introduced prior to membrane deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Pilbat et al [139] reported a method to immobilize cell membrane bilayers of DPPC in LbL films of poly-(glutamic acid)/poly(lysine) (PGA/PLL). The film growth regime was altered by inserting a DPPC bilayer in between the polyelectrolyte bilayers because this DPPC bilayer blocked diffusion for the next PGA/PLL layers.…”
Section: Films Deposited On Solid Substratesmentioning
confidence: 99%